Dangerous familiars : representations of domestic crime in England, 1550-1700 - Dolan, Frances E. (Frances Elizabeth), 1960- (Book collections on Project MUSE., 1994)
Even now in the mass media, women are often portrayed as murderers in their own homes, although in reality women are much more likely to be the victims of domestic violence than the perpetrators. Looking back at images of violence in the popular culture of early modern England, we find similar misperceptions. The spector of the murderer loomed most vividly not in the stranger, but in the familiar; and not in the master, husband, or father, but in the servant, wife, or mother. A gripping exploration of seventeenth-century accounts of domestic murder in fact and fiction, this book is the first to ask why. The author examines stories ranging from the profoundly disturbing to the comically macabre: of husband murder, wife murder, infanticide, and witchcraft. She surveys trial transcripts, confessions, and gallows speeches, as well as pamphlets, ballads, and popular plays based on notorious crimes. Citing contemporary analogies between the politics of household and commonwealth, she shows how both legal and literary narratives attempt to restore the order threatened by insubordinate dependents. -- from Publisher description.